PENELITIAN CONTINUOUS AUDITING DAN MONITORING UNTUK MASA DEPAN MENGGUNAKAN ANALISIS BIBLIOMETRIK - Desy Elevany Sera; Fitriana Fitriana; Rachmat Agus Santoso (LPPM Universitas Bina Bangsa, 2024)
This study aims to further examine the concept of implementing continuous auditing and monitoring (CACM) to provide broader insight and can reduce audit audit costs, enabling internal auditors to provide more accurate and timely audit report results. With bibliometric analysis collected from the Scopus database of 240 documents from 2010 to 2020. The research method uses bibliometric analysis. An application system for data visualization using VOSviewer. Continuous Auditing and Monitoring (CACM) research is still little found because the concept was socialized by BPKP through the National Seminar-AAIPI in 2016. Research by the Deputy of Bappenas shows that the application of the CACM concept currently requires more management support in the form of regulatory availability and integrated application system support that is able to produce quality information or data to meet audit needs more effectively. This research can be a guideline for future researchers to conduct research on the application of continuous auditing and monitoring (CACM) for internal auditors to carry out internal control and assessment of risk management in an organization. Bibliometric analysis of the concepts of continuous auditing and monitoring with Scopus data is still difficult to find. This research provides new insights into the concept of implementing continuous auditing and monitoring so that it can be useful in evaluating internal control and appropriate risk assessment in the government sector in Indonesia